Konflik Identitas dan Budaya Antar Suku di Yogyakarta, Heterogenisasi Vs Homogenisasi : (Dinamika Peran Keraton dan Filosofi Keistemewaan Yogyakarta dalam Menangani Konflik) - Muhammad Rouf Mustofa; Ita Rodiah (JURNAL SOSIAL, 2024)
Student groups or communities living in Yogyakarta create fuses that can catch fire at any time. Groups in Yogyakarta have the potential to experience offense caused by various aspects. The frequent occurrence of identity and ethnic conflicts is quite disturbing, especially for indigenous people. Yogyakarta society is facing the challenge of homogeneity in particular, long before theories and studies about the dangers of homogeneity, there were several special philosophies that the Yogyakarta people always adhered to in carrying out their life roles. The role of the Palace and the implementation of the special philosophy in Yogyakarta has not been fully understood by most people, especially immigrants. The collaboration between the religious patterns of Yogyakarta society and the philosophy of privilege is very closely related to the concept of Islam Nusantara. Indirectly, it is hoped that such collaboration with the heterogeneous society of Yogyakarta can reduce homogenization conflicts, both religious and cultural. One of them is the "Imaginary Axis". The Imaginary Axis is visualized in the form of three special places in Yogyakarta which include Mount Merapi, Tugu Yogyakarta, Keraton, Panggung Krapyak, and South Beach. The Imaginary Axis symbolizes harmony and balance in nature. Nature here consists of five aspects, namely fire from Mount Merapi, soil from the earth of Nga-Yogyakarta, air from the South Coast, wind, and space. So the Imaginary Axis philosophy can be interpreted as a harmonization between the environment and the physical, namely balance in the relationship between humans and God, humans and fellow humans, and humans and nature. This article reviews the relationship between religion and culture with the Yogyakarta philosophical axis using a phenomenological literature review data analysis framework.